Pengaruh Suhu Perkerasan Terhadap Umur Perkerasan Lentur Menggunakan Metode Analitis - Nola Riwibowo; Fibia Sentauri Cahyaningrum; Taruna Firlian Tama; Friska Amelia (Universitas Trunojoyo Madura, 2023)
This study will discuss the effect of temperature design with variations in air temperature between 24 ÂºC and 30 ÂºC on the life of flexible pavements. The obtained secondary field data was processed using the Nottingham Design Method. Furthermore, the results of the data processing are used to calculate the strain value with the BISAR 3.0 program (Bitumen Stress Analysis in Roads). The strain values resulting from the BISAAR 3.0 program analysis in the form of asphalt mix horizontal tensile strain (Îµt) and subgrade vertical strain (Îµz) are used to calculate the life of flexible pavements. The results of the analysis show that when using fatigue crack damage criteria, a temperature increase of 5.8% will cause a decrease in the life of flexible pavement by 0.7% (critical condition) or 0.6% (failed condition). However, when using the criteria for permanent deformation damage, a temperature increase of 5.8% will reduce the life of flexible pavement by 1.5% (critical condition) or 1.0% (failure condition).